The Effects of Rental Assistance Programs on Neighborhood Outcomes for U.S. Children: Nationwide Evidence by Program and Race/Ethnicity - Fenelon, Andrew; Slopen, Natalie; Newman, Sandra J. (Urban affairs review (Thousand Oaks, Calif.), 2023)
Project-based housing programs and tenant-based housing programs (vouchers) may have differential effects on neighborhood outcomes for residents. Theoretically, vouchers should enhance access to low-poverty neighborhoods for low-income families thereby promoting economic mobility for children, though vouchers’ success may vary by race and ethnicity. Drawing on a national survey-administrative data linkage and a quasi-experimental approach, we examine the impact of project-based housing and vouchers on an index of socioeconomic neighborhood disadvantage among children. We find that living in project-based housing leads to greater exposure to neighborhood disadvantage while receiving vouchers leads to reduced exposure. Reductions in neighborhood disadvantage for children receiving vouchers are found only for non-Hispanic Black and Hispanic/Latino children. For non-White families, vouchers are associated with a reduced likelihood of living in high-poverty neighborhoods and increased likelihood of living in low-poverty neighborhoods, presenting an opportunity to narrow racial and ethnic differences in children's neighborhood attainment.